If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 7 = -26 Reorder the terms: 7 + 11x = -26 Solving 7 + 11x = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 11x = -26 + -7 Combine like terms: 7 + -7 = 0 0 + 11x = -26 + -7 11x = -26 + -7 Combine like terms: -26 + -7 = -33 11x = -33 Divide each side by '11'. x = -3 Simplifying x = -3
| -12.26-15.5h=-1.7+15.34-7.8h | | -6(u+9)=-9u-36 | | Y-19.27=-4.27 | | X-9=(-30) | | 9(4-x)=7(x-3) | | 30+x^2-11x=0 | | 8w+41=-9(w+3) | | 20+3x(-4)-2x(-5)= | | 0=-3x^2+2x | | 3x+16=8x+3 | | -2(k-7)-(-3k-7)=7 | | 7.5y=112.5 | | 12+x^2-8x=0 | | 16 = c4+ 13 | | 4(12x+2)-20=10x+12 | | 1/10.19=12/n | | 1/10.19=12n | | -1/4c=20 | | cos(18)=20/X | | 7-(2x-5)=3(2x+4) | | 7-(2-5)=3(2x+4) | | 6y-8=2y+20 | | 13-3x=7x+7-9x | | 2(2p+4)=-6(p+7) | | Y^2+2y+312=0 | | 6x-3y=-6x | | 4x+8.40=7+7.15 | | 42/7= | | 10+3f=4 | | 10x+12=4x+36 | | -3(x+4)+15=-6-4x | | Y/2.25=4 |